Analysis of Sports Event Management Teaching from the Perspective of Multimedia considering Multiobjective Teaching Optimization Algorithm - Rongrong Wang (Advances in Multimedia)
At present, the combination of multimedia technology and physical education has been extensively applied, and the reform of sports event management has also attracted the attention of researchers. Reform and innovation have been carried out on the effective utilization of physical education resources and the image display of sports actions with great difficulties in the process of teaching and cross school and class synchronous learning, which has not only enriched the approaches and methods of sports management and teaching but also achieved certain effects.